The Role of Cannabinoids in the Treatment of Skin Diseases: A Review of Mechanisms of Action and Clinical Evidence - Marciniak, Kinga; Jurczuk, Aleksandra; Olszanska, Monika; Rafałowicz, Adam (Journal of Education, Health and Sport, 2025)
Cannabinoids derived from Cannabis sativa L., particularly cannabidiol (CBD) and minor cannabinoids such as cannabigerol (CBG), cannabichromene (CBC), tetrahydrocannabivarin (THCV), and cannabidivarin (CBDV), have attracted increasing interest due to their potential therapeutic properties in dermatology. These compounds exert anti-inflammatory, antimicrobial, immunomodulatory, sebostatic, and antiproliferative effects, which may benefit a range of skin conditions. Preclinical and early clinical data suggest that cannabinoids may effectively alleviate inflammation, pain, pruritus, and microbial infections in various dermatologic disorders. Topical and transdermal routes show promise due to improved safety and targeted delivery. CBD has demonstrated efficacy in reducing sebum production in acne, modulating immune responses in psoriasis, and accelerating wound healing in EB. However, findings for alopecia areata remain inconsistent. Emerging delivery systems, including CBG-based emulgels and CBD transdermal patches, may improve local bioavailability and clinical outcomes. Cannabinoids, especially CBD, exhibit significant potential as adjuvant or alternative treatments for inflammatory, infectious, and autoimmune skin diseases. Despite promising preliminary results, large-scale, randomized, placebo-controlled trials are needed to establish optimal dosing, formulations, safety, and long-term efficacy in clinical dermatology.